2010
DOI: 10.1103/physrevlett.105.166601
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Transport in Dual-Gated Bilayer Graphene at Large Displacement Fields

Abstract: We study the electronic transport properties of dual-gated bilayer graphene devices. We focus on the regime of low temperatures and high electric displacement fields, where we observe a clear exponential dependence of the resistance as a function of displacement field and density, accompanied by a strong non-linear behavior in the transport characteristics. The effective transport gap is typically two orders of magnitude smaller than the optical band gaps reported by infrared spectroscopy studies. Detailed tem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

26
248
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(275 citation statements)
references
References 35 publications
26
248
1
Order By: Relevance
“…However, band gaps determined from conventional electronic transport measurements are smaller than theoretically expected or extracted from the optical measurements by an order of magnitude or more 7,8,13,[22][23][24][25] . Recently, it has been suggested that disorder-induced localized states inside devices or along the edges can introduce additional conducting channels inside the gap, consequently reducing the effective gap seen in transport measurements [23][24][25] . Additionally, 3 many-body interactions in bilayer graphene, which can be sensitive to local electrostatic variations such as disorder potential fluctuations, are expected to open a gap even in zero applied field 11,17 .…”
mentioning
confidence: 97%
“…However, band gaps determined from conventional electronic transport measurements are smaller than theoretically expected or extracted from the optical measurements by an order of magnitude or more 7,8,13,[22][23][24][25] . Recently, it has been suggested that disorder-induced localized states inside devices or along the edges can introduce additional conducting channels inside the gap, consequently reducing the effective gap seen in transport measurements [23][24][25] . Additionally, 3 many-body interactions in bilayer graphene, which can be sensitive to local electrostatic variations such as disorder potential fluctuations, are expected to open a gap even in zero applied field 11,17 .…”
mentioning
confidence: 97%
“…Although infrared spectroscopy measurements yield large band gaps of up to 250 meV, 42 the strong role played by disorder limits the expected strong suppression of charge transport measurements and results in only a few meV as the effective transport gap. 43 Figure 5a shows the 2D plot of the local resistance as a function of V BG and V TG . Near the charge neutrality point, the device resistance increases approximately fivefold as the total displacement electric field is increased.…”
Section: Spin Transport In Bilayer Graphenementioning
confidence: 99%
“…For instance, electrical conductance experiments [11][12][13] have confirmed the existence of a finite QP band gap but their measured value is disturbed by many extrinsic factors, e.g., the inevitable contact resistance between the electrodes and graphene sheet. While noncontacting optical measurements [8][9][10] have revealed a tunable band gap in GBLG, these results are indirect because the optical absorption peak (edge) is not conceptually equivalent to the QP band gap 14,15 .…”
mentioning
confidence: 99%
“…One promising approach is to apply the gate electric field perpendicular to the AB (Bernal) stacked bilayer graphene (BLG) to break the inversion symmetry of sublattices 6,7,[9][10][11] . Such an induced band gap of GBLG can be tuned in a wide range by field strength 9,[11][12][13] , offering an important degree of freedom to optimize performance of graphene devices.…”
mentioning
confidence: 99%